2009
DOI: 10.1007/s00213-009-1482-y
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of dopamine receptors to periaqueductal gray-mediated antinociception

Abstract: Rationale Morphine relieves pain, in part, by acting on neurons within the periaqueductal gray (PAG). Given that the PAG contains a subpopulation of dopamine neurons, dopamine may contribute to the antinociceptive effects mediated by the PAG. Methods This hypothesis was tested by measuring the behavioral and electrophysiological effects of administering dopamine agonists and antagonists into the ventrolateral PAG (vPAG). An initial histological experiment verified the existence of dopamine neurons within the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
60
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(64 citation statements)
references
References 46 publications
3
60
0
1
Order By: Relevance
“…These findings were consistent with previous studies which showed that selective D2-like dopamine receptor antagonists systemically attenuated the analgesia induced by systemic amphetamine, morphine and cocaine in the formalin test [38,39]. Moreover, the antinociceptive effects of apomorphine were blocked by the D2-like receptor antagonist, eticlopride [40]. In line with this, administration of a selective D2-like dopamine receptor agonist intracerebroventricularly or in the striatum produced antinociceptive effects [19,41].…”
Section: Discussionsupporting
confidence: 91%
“…These findings were consistent with previous studies which showed that selective D2-like dopamine receptor antagonists systemically attenuated the analgesia induced by systemic amphetamine, morphine and cocaine in the formalin test [38,39]. Moreover, the antinociceptive effects of apomorphine were blocked by the D2-like receptor antagonist, eticlopride [40]. In line with this, administration of a selective D2-like dopamine receptor agonist intracerebroventricularly or in the striatum produced antinociceptive effects [19,41].…”
Section: Discussionsupporting
confidence: 91%
“…In addition, microinjection of SKF-38393into the ventrolateral orbital cortex did not exhibit any effects on formalin induced nociceptive behaviors [8]. Another study also showed that the antinociceptive effects of apomorphine were blocked by administration of eticlopride, D2-like receptor antagonist, but notSCH-23390 into the periaqueductal gray [16]. These inconsistent results may be due to different reasons such as, protocol (models of pain induction), animal models, and the brain areas investigated.…”
Section: Discussionmentioning
confidence: 88%
“…Dopamine neurons may communicate with neural areas that are involved in the affective aspects of pain [105,106]. Dopaminergic neuron depletion in the vPAG with 6-hydroxydopamine (6-OHDA) decreases opioid-induced antinociception in rats [107], and a more recent study suggests that dopamine may have a direct antinociceptive effect in addition to the modulation of the antinociceptive effects of morphine [108]. Both D 1 and D 2 dopamine receptors are expressed by PAG neurons; the former receptors are associated with morphine analgesia [107] and the latter receptors are associated with dopamine analgesia [108].…”
Section: General Mechanistic Discussionmentioning
confidence: 98%
“…Dopaminergic neuron depletion in the vPAG with 6-hydroxydopamine (6-OHDA) decreases opioid-induced antinociception in rats [107], and a more recent study suggests that dopamine may have a direct antinociceptive effect in addition to the modulation of the antinociceptive effects of morphine [108]. Both D 1 and D 2 dopamine receptors are expressed by PAG neurons; the former receptors are associated with morphine analgesia [107] and the latter receptors are associated with dopamine analgesia [108]. It has been suggested that there are synaptic connections between dopaminergic and GABAergic neurons in the vPAG, which implicates the participation of dopaminergic neurons in analgesia.…”
Section: General Mechanistic Discussionmentioning
confidence: 99%